Candidate Gender Quotas: A Framework for Analysis - Mona Lena Krook (My University, 2016)
Quotas for women in politics have diffused rapidly around the globe in recent years, with political parties and national legislatures in more than a hundred countries adopting—or debating the adoption of—reserved seats, party quotas or legislative quotas to increase the selection of female candidates to political office. These developments have sparked an explosion of research on candidate gender quotas. However most of this work focuses on single cases and reflects little awareness of developments in other countries around the world. As a result, the findings in one case are often contradicted in other studies, revealing few clear patterns with regard to the origins and outcomes of gender quota policies. To foster a more cumulative research agenda, this article approaches quotas as a global phenomenon and elaborates a framework for analyzing and comparing the actors, motivations and contexts at work in specific quota reforms.